A BLENDED APPROACH TO LEARNING IN MODERN EDUCATION Komila Eshmakhmatovna Turaboeva Karshi engineering - economics institute, teacher at the Department of Foreign Languages Abstract: Blended learning is an educational concept in which the student gains kno (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Blended learning is an educational concept in which the student gains knowledge both independently online and face-to-face with a teacher. This approach makes it possible to control the time, place, pace and path of learning the material. Blended education allows the teacher to combine traditional methods and modern technologies.